2014
DOI: 10.1111/cdoe.12101
|View full text |Cite
|
Sign up to set email alerts
|

Daily smoking and 4‐year caries increment in Finnish adults

Abstract: Daily smoking was independently related to caries development (net DT increment) in adults over 4 years, but not to caries treatment (net FT and MT increments) or caries experience (net DMFT increment).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
7
22
0
1
Order By: Relevance
“…Smoking correlated with untreated decayed teeth in this study. This is consistent with previous reports 15,16) . Bernabe et al 16) investigated the relationship between daily smoking and caries increment in adults.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Smoking correlated with untreated decayed teeth in this study. This is consistent with previous reports 15,16) . Bernabe et al 16) investigated the relationship between daily smoking and caries increment in adults.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous reports 15,16) . Bernabe et al 16) investigated the relationship between daily smoking and caries increment in adults. They found that daily smoking was related to net decayed teeth (DT) increment over a 4-year period but not to net filled teeth (FT), missing teeth (MT), or DMFT increments.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Smoking was correlated with untreated decayed teeth in this study. Bernabe et al 9) investigated the relationship between daily smoking and caries increment in adults. They found that daily smoking was related to the net decayed teeth increment but was not related to the net filled teeth, missing teeth, or decayed, missing, and filled teeth increments over a 4-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking status was derived from answers to four questions: “have you ever smoked?,” “have you ever smoked regularly (daily for at least 1 year),” “have you smoked at least 100 times?” and “when did you last smoke?” Daily smokers were those who met all following conditions: smoked at least 100 times in their lifetime, regularly for at least 1 year and most recently the day of the survey or the previous day (WHO, ). This definition has been used in previous analysis of the same data (Kanhai et al., ; Bernabe, Delgado‐Angulo, Vehkalahti, Aromaa, & Suominen, ; Sabbah, Suominen, Vehkalahti, Aromaa, & Bernabe, ). Dental attendance pattern was reported on a 3‐point response scale (regularly for check‐ups, only when in trouble or never).…”
Section: Methodsmentioning
confidence: 99%